Germinação in vitro de Pinus taeda L. a partir de sementes selecionadas - Golle, Diego Pascoal (2007)
Pinus taeda L. is among the more planted forest species in Brazil due its desirable characteristics of production and industrial quality. Currently, it has been necessary to be developed techniques that make possible the massal production of improved genotypes and the tissue culture techniques offer this possibility. Gotten plants in vitro from seeds possess two important characteristics: the youthfully and the existing variability in lots of seeds. The objective of this work was to evaluate methods of choice of lots of seeds from its characteristics of health and vigor; to optimize the germination and to establish this forest species in vitro. Seeds of three lots supplied by the Klabin Company, deriving of clone orchards of called seeds Celucat (1st Generation), Igaras (1st Generation) and Igaras (2nd Generation) were submitted the sanitary tests through the technique blotter-test ; and analyses of vigor based in the performance of seedling evaluated the variables: hard seeds dead seeds, abnormal seedling, weak normal seedling and heavy normal seedling. Of this last one, it was effected the analysis of the length (cm), fresh weight (g) and dry weight (g). For disinfestations, six treatments had been tested, that were composites of three combinations of disinfestations times and concentration of NaOCl, beyond presence or absence light during first days of the experiment. The seeds were germinated in MS medium (MURASHIGE e SKOOG, 1962). The germination of the seeds in alternative substrata of paper was also tested like filter paper, starch and starch combined with agar at a first moment and, later, the germination in substratum of medium MS with activated charcoal and liquid medium MS having vermiculite as gelling agent. The substrata filter paper, hydrophilic cotton and agarwater had been evaluated how much to the water subsidy that they supply the seeds. As treatment pre-germinative, it was carried through experiments with different times of soak and germination in hydrophilic cotton. The establishment was also evaluated in vitro from node cotyledonar in media MS, WPM (LLOYD e McCOWN, 1981) and reduced MS to the half of the concentration of mineral salts. The health tests had been efficient in the discrimination of the lots, has been more representative the genera Fusarium, Penicillium and Trichoderma. In the same way, variable of the vigor: abnormal seedling, heavy normal seedling and length, dry weight and fresh weight of heavy normal seedling had allowed the stratification of the lots. The disinfestations in 3% NaOCl during 5 minutes and 4% during 3 minutes had demonstrated the best ones performances; however, NaOCl presented toxic to the seeds, inhibiting the germination. The media with different substrata had not presented significant differences for the germination of the seeds. Through the analysis of the water absorption in different substrata it was possible to establish the soak curves and to compare substrata in relation to water suply. The soak for 72 hours of the seeds and posterior inoculation in hydrophilic cotton was efficient in the germination of seeds. It was possible to in vitro establish plants of Pinus taeda L. but the analyses statistics had not demonstrate differences among the media tested for such purpose.